L’utilizzo di ceppi modificati di saccharomyces cerevisiae in enologia - Schuller, Dorit Elisabeth (2006)
Trata-se de uma tradução do seguinte artigo D. Schuller e M. Casal. 2005. The use of genetically modified yeast in the wine industry. Applied Microbiology and Biotechnology 68, 292-304.